"Methods and Tools of Speech Development of Small Group Children in Preschool Education Organization" (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Implementation of the methods and methods used in the elimination of speech defects in children of a small group in a preschool educational organization.